Functioning transferred free muscle innervated by part of the vascularized ulnar nerve connecting the contralateral cervical seventh root to themedian nerve: Case report - Kakinoki, Ryosuke; Ikeguchi, Ryosuke; Nakayama, Ken; Nakamura, Takashi (Journal of Brachial Plexus and Peripheral Nerve Injury, 2007)
Background The limited nerve sources available for the reconstruction and restoration of upper extremity function is the biggest obstacle in the treatment of brachial plexus injury (BPI). We used part of a transplanted vascularized ulnar nerve as a motor source of a free muscle graft.Case presentation A 21-year-old man with a left total brachial plexus injury had received surgical intercostal nerve transfer to the musculocutaneous nerve and a spinal accessory nerve transfer to the suprascapular nerve in another hospital previously. He received transplantation of a free vascularized gracilis muscle, innervated by a part of the transplanted vascularized ulnar nerve connecting the contralateral healthy cervical seventh nerve root (CC7) to the median nerve, and recovered wrist motion and sensation in the palm. At the final examination, the affected wrist could be flexed dorsally by the transplanted muscle, and touch sensation had recovered up to the base of each finger. When his left index and middle fingers were touched or scrubbed, he felt just a mild tingling pain in his right middle fingertip.Conclusion Part of the transplanted vascularized ulnar nerve connected to the contralateral healthy cervical seventh nerve root can be used successfully as a motor source and may be available in the treatment of patients with BPI with scanty motor sources.